Global commerce and human rights: towards an African legal framework for corporate human rights responsibility and accountability - Osuntogun, Abiodun Jacob (My University, 2016)
Since the 1970s, when third world countries challenged the market-dominated international trade regime, the United Nations (UN) has been engaging without relent on how to fill the gap in business and human rights governance. The gap exists in countries with relaxed domestic regulatory regimes, where multinational corporations commit human rights violations without regional and institutional mechanisms to hold them accountable. From the draft codes, to the Global Compacts and the UN Draft Norms, the search failed to yield the desired result. In 2005, another move was made that produced a compendium of UN Guiding Principles on Business and Human Rights (UNGP) which was unanimously endorsed by the UN Human Rights Council (UNHRC) in May 2011. Although it has been argued that the endorsement fills the gap that has been missing in the quest for global corporate accountability, the search continues unabated at the UN forum albeit without the support of some powerful nations for a ‘binding international legal instrument’ that will regulate the activities of corporations with regard to human rights. However, while awaiting the outcome of the recent interrogation on the issue, the UNHRC passed a resolution that the implementation of the UNGP should commence. Since Africa is one of the continents greatly affected by this problem, this thesis considers how the African Union (AU) can develop a framework for corporate human rights responsibility and accountability in line with the UNGP. To this end this thesis proposes a mechanism that will engender a proper implementation of the UNGP; it argues that a new treaty process and implementation of the UNGP are simply different sides of the same coin and that they serve the same purpose. The thesis also considers the adequacy of the existing regulatory framework for corporate human rights accountability in Africa and explores the creation of an appropriate forum for the implementation of the UNGP. Choosing the AU as the suitable forum, this thesis endeavours to examine how some legal and policy-making institutions in the AU can be rejuvenated, overhauled and re-positioned in order to perform effective corporate accountability oversight to support the domestic and sub-regional systems. Furthermore, it attempts to provide possible remedies to victims of corporate human rights violations in Africa.
Thesis submitted in fulfilment of the requirements for the degree of (PhD) in the School of Law at the University of the Witwatersrand School of Law Faculty of Commerce, Law and Management University of the Witwatersrand, Johannesburg
Keywords: International law; Human rights; MUltinational enterprises; Africa; African Union; Corporate accountability